2016
DOI: 10.15446/rsap.v18n2.49237
|View full text |Cite
|
Sign up to set email alerts
|

Exposición de peatones a la contaminación del aire en vías con alto tráfico vehicular

Abstract: Objective To describe the demographic, social, physical and mental health factors associated with the functional capacity of older adults in the Department of Antioquia in 2012. Materials and Methods A descriptive study with the records of 4 248 adults aged 60 years or more as the population, surveyed in the Department of Antioquia, in 2012. They were asked about their functional capacity through a Katz survey consisting of 6 items. With the independent variables, frequency measurements were calculated, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
(11 reference statements)
0
3
1
3
Order By: Relevance
“…The functional capacity levels found in the study were lower than those found in a sample of Brazilian, Colombian and Polish elderly women [8,21,22]. According to the normative references of Rikli and Jones [10], the elderly women in our study had belownormal results in an index between weak and very weak.…”
Section: Resultscontrasting
confidence: 79%
“…The functional capacity levels found in the study were lower than those found in a sample of Brazilian, Colombian and Polish elderly women [8,21,22]. According to the normative references of Rikli and Jones [10], the elderly women in our study had belownormal results in an index between weak and very weak.…”
Section: Resultscontrasting
confidence: 79%
“…Levels of schooling are similar to those reported in a study that demonstrated that schooling levels in the majority of this population vacillate around 5 years, Biopsychosocial Characteristics of Elderly Adults of Latin America: Strategies of Physical… DOI: http://dx.doi.org/10.5772/intechopen.99476 which is a possible cause of the above-mentioned higher number of women who dedicate the majority of their time to households and may come across fewer opportunities to finish basic studies [35]. Schooling levels were higher in the research with 84% of SCs having finished elementary school [36], as well as in the study with 66.4% of SCs having finished elementary school [37]. This data may be attributed to the higher number of male participants in these studies, which for cultural reasons present with a higher education level.…”
Section: Personal Characteristics: Sociodemographicmentioning
confidence: 99%
“…When reviewing the numbers based on category, mild and moderate cognitive deterioration was less compared to those in elderly's in Antioquia (mild deterioration at 49.6% and moderate deterioration at 31.5%). The higher rates of risk of mild or moderate cognitive deterioration may be related to the fact that elderly' s present with higher rates of depression [37] in addition to the prevalence of morbidity higher than three ailments, which could function ace to risk for factor decrease in functionality, occurrence of depression, and cognitive deficit [46]. The risk data for cognitive deterioration are similar for elderly' s in this study and those in Queretaro, Mexico, which was expected because the variables of age, schooling, and the existence of chronic ailments in these studies presented related prevalence [47].…”
Section: Psychological Characteristicsmentioning
confidence: 99%
“…En la actualidad la emisión de gases del parque automotor genera la contaminación del aire que viene siendo uno de los problemas ambientales más severos (MINAM, 2014); siendo la contaminación del aire una amenaza aguda, acumulativa y crónica para el medioambiente (Segura-Contreras & Franco, 2016), mostrando efectos adversos a la salud humana (Ballester Díez et al, 1999). Los problemas de contaminación del aire son reconocibles en una amplia gama de escalas espaciales, siendo quizás el más pequeño de estos a la escala de calles (Harrison et al, 2014).…”
Section: Introductionunclassified